Cognitive impairments in patients with hematological malignancies prior and after allogeneic hematopoietic stem cells transplantation - D. E. Vybornykh; S. Yu. Fedorova; S. O. Khrushchev; M. Yu. Drokov; E. G. Gemdzhian; L. A. Kuzmina; E. N. Parovichnikova (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева, 2019)
The treatment of patients with hematological malignancies is often complicated by a number of negative side effects, which include mental disorders, among which cognitive impairment occupies a special place. Psychopathological, psychological, neuropsychological, neurophysiological and neurovisual methods were used to examine 46 patients with various hematological malignancies during periods prior to allo-HSCT, 1-3 months after allo-HSCT, and 6 months after transplantation. When statistical analysis of data was performed correlation and multivariate analyzes. Patients at each stage of the study identified cognitive impairment caused by a combination of risk factors — the presence of a hematological malignancy, the encephalotropic activity of chemotherapy drugs, and mental, neurological disorders. The characteristic and stable dynamics of CN in the post-transplantation period is traced — a sharp decline in cognitive functions in almost all indicators at once in the early post-transplant period with their gradual recovery by 6 months after allo-HSCT. The attitude of patients to cognitive deficiency also changes during the period of treatment: from anozognosic and hyponozognosic at the pre-transplantation stage to hypernosognostic at long-term periods after allo-HSCT.